Multicenter review of a tadalafil suspension formulation for infants and children with pulmonary hypertension: A North American experience - Youssef, David Edward; Handler, Stephanie S.; Richards, Susan Marjorie; Sheppard, Catherine Anne; Smith, Jenna; Tillman, Kathryn; Pietrosanu, Matthew; Kirkpatrick, Edward; Bates, Angela (Frontiers in Pediatrics, 2023)
Introduction: Phosphodiesterase type 5 (PDE5) inhibitors, with sildenafil the earliest among them, are widely used in the management of pediatric pulmonary arterial hypertension (PAH). Tadalafil is a PDE5 inhibitor with a long half life (16 hours), stable pharmacokinetics and pharmacodynamics, and minimal adverse effects. However, the utility of tadalafil suspensions in this setting has not been widely explored due to a lack of clinical experience. We present a multicenter experience that details the safety and tolerability of a tadalafil suspension, either alone or in combination with another vasodilator, for the management of pediatric pulmonary hypertension (PH).